PENGGUNAAN ZMIJEWSKI'S SCORE DAN SPRINGATE'S SCORE UNTUK MEMPREDIKSI KINERJA PERUSAHAAN DALAM KONDISI KRISIS EKONOMI - Anis Al Rosjidi (Jurnal Fokus Manajemen Bisnis, 2021)
The Covid-19 pandemic has deteriorated the company's performance in the restaurant, hotel, tourism and transportation sectors. However, some companies are still able to survive by continuing to show positive performance. Using a sample of 54 companies in the restaurant, hotel, tourism, and transportation sectors, this study examines whether the Zmijewski score and the Springate score (which is commonly used to predict bankruptcy) can also be used to predict performance in times of crisis. This study shows that the Zmijewski score and the Springate score can be used. Zmijewski's score is negatively related to the company's profitability during the crisis, while the Springate's score is positively related to the company's profitability during the crisis. This study shows that the bankruptcy prediction score can be extended to predict the company's performance in times of crisis.